A Field Guide to the Geology of Western Ireland The Birth and Death of an Ocean - Ryan, Paul D. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book contains a comprehensive field guide, including detailed itineraries and supporting data, to the Geology of Western Ireland, a classic site for world geology. It facilitates study into the rock record of the Neoproterozoic 'birth' to the Devonian 'death' of the Iapetus Ocean along the Laurentian (North American) margin. The enormous variety of lithologies and processes available for study in this spectacularly exposed region include: fluviatile to deep-sea sediments; layered ultramafic intrusions to reverse zoned granite batholiths; zeolite to eclogite facies metamorphic assemblages; continental rifting; subduction processes; island arc evolution; arc-continent collision; Andean margin development; and continent-continent collision. An introduction to the geology, that includes information relevant to the planning and execution of field trips in the region, is followed by nine chapters each providing the necessary background, field itineraries, exercises and points for debate, covering: the Laurentian basement and Neoproterozoic cover of North Mayo, Sligo, the Ox Mountains and Connemara; the metamorphic nappes and syn-orogenic intrusions of the Ordovician Grampian Orogeny; the Cambro-Ordovician subduction-accretion complex of Clew Bay; the obducted Ordovician fore-arc basin of South Mayo; the post-subduction flip late-Ordovician of South Connemara; the Silurian successor basins deformed during the final closure of the Iapetus Ocean; the late to post-orogenic Devonian sediments; the Devonian Granite batholiths ; and the post-orogenic Carboniferous cratonic sediments. Two final chapters summarise: the current tectonic interpretation of this region; areas for future research; and the extensive sources of geochemical and geophysical data.
Chapter 1 - Introductory section with history of research and philosophy of the guide -- Chapter 2 - The basement and Neoproterozoic rocks of North Mayo and the Ox Mountains -- Chapter 3 - The metamorphic fold nappes and syn-orogenic intrusions of Connemara -- Chapter 4 - The subduction-accretion complex and dismembered ophiolite of Clew Bay -- Chapter 5 - The Ordovician fore-arc and arc complex and the Silurian back-arc basin of South Mayo -- Chapter 6 - The post-orogenic Devonian and Carboniferous deposits -- Chapter 7 - The Devonian Granite batholiths, their emplacement and mineralisation -- Chapter 8 - Final section summarising admissible tectonic interpretations and areas of debate.
Keywords: Geology; Geodynamics; Petrology; Geology; Geodynamics; Petrology